The relationship between radar scattering and surface roughness of lunar volcanic features. Issue 11 (17th November 2014) - Jawin, Erica R.; Kiefer, Walter S.; Fassett, Caleb I.; Bussey, D. Benjamin J.; Cahill, Joshua T. S.; Dyar, M. Darby; Lawrence, Samuel J.; Spudis, Paul D.
Abstract Lunar roughness measurements derived from the Lunar Orbiter Laser Altimeter are compared to 12.6 cm wavelength radar data collected by the Miniature Radio Frequency instrument and 70 cm wavelength radar data collected by the Arecibo Observatory. These data are compared to assess how surface and subsurface roughness are correlated and affected by parameters including age and composition at length scales between 0.1 and 100 m. A range of features are analyzed including volcanic domes (Marius Hills, Rümker Hills, Gruithuisen, and Mairan Domes); mare (Imbrium, Serenitatis, and Oceanus Procellarum); pyroclastic dark mantle deposits (Sinus Aestuum, Sulpicius Gallus, and Mare Vaporum); and two young craters (Copernicus and Tycho). Statistically significant positive correlations exist between topographic roughness and both P‐ and S‐band circular polarization ratios. The strongest correlation is observed at the longest length scales. Correlations weaken as length scales become less similar, potentially due to distinct processes controlling surface modification. Roughness is not significantly correlated with local slope. Although the Marius Hills are compositionally distinct from the Gruithuisen and Mairan domes, they are indistinguishable in roughness characteristics. Conversely, the Rümker Hills, mare, and dark mantle deposits are smoother at the length scales examined, possibly due to fine‐grained mantling of regolith or pyroclastic deposits. The floor and ejecta of Tycho are the roughest surfaces measured in this study, while the floor and ejecta of Copernicus overlap the roughness distribution of the volcanic features. This study shows that many factors control the evolution of roughness over time on various length scales.